Identification of Educational Staff Performance Problems Related to Digital Competence with Front-End Analysis - Rahmat Dwi Gunawan; Eveline Siregar; Uwes Anis Chaeruman (Teknodika, 2025)
Presidential Regulation of the Republic of Indonesia Number 82 of 2023 concerning the acceleration of digital transformation and integration of national digital services implicitly instructs bureaucratic officials within an organization to immediately change the way they work and develop individuals within the organization to adapt to the new digital era. The research aims to identify performance problems related to digital competence and their causes, determine whether there are performance gaps that occur, and identify alternative solutions that can be used to overcome performance gaps at the Office Deputy of the National Level Leader-Education of Lemhannas RI (The National Resilience Institute of the Republic of Indonesia). The research employed the Joe Harless performance analysis model with data collection technique in the form of a survey involving 23 education staff and continued with observations and interviews to complete and confirm the data from the survey answers. The research results show that designing and providing digital competence training is an alternative solution that relevant organizations may choose to improve the digital competence of education staff by considering the digital competence areas that have been suggested in the research complete with alternative digital technologies that have been delivered so that the training designed can be in accordance with the identification of existing needs. The results of the research may be implemented in determining the appropriate development activities for human resources at the Office Deputy of the National Level Leader-Education of Lemhannas RI, especially to improve digital competence as an effort to address organizational transformation in the era of digitalization.